Shadow Banking : Economics and Policy - Claessens, Stijn (Staff Discussion Notes; Staff Discussion Notes ;, 2012)
This note outlines the basic economics of the shadow banking system, highlights (systemic) risks related to it, and suggests implications for measurement and regulatory approaches.